TAHLĪL WASᾹIT LECTORA INSPIRE FĪ TATHWĪR TA’LĪM LUGHAH ‘ARABIYYAH - Zidni, Salma Izza; Kotta, Kamila Maryam Kotta Maryam; Nabila, Amirotun Nabila (STIQ Amuntai, 2023)
In this era of globalization, there have been many rapid developments in all human activities. The influence of this all-digital era forces all experts to switch and focus on technology. From the economic and the social to the education. In learning, teachers are required to create innovative and more exciting learning. One way to create innovative and enjoyable learning is to use learning media. One of the learning media currently being developed by the world of education is interactive multimedia Lectora Inspire. This study aims to explain the use of Lectora Inspire media in learning Arabic for class XII at Madrasah Aliyah Negeri. This study used the library research method. This research results in learning using the Lectora Inspire media becomes more interactive because it can use text, sound, video, and animation in one unit. Then be able to visualize abstract material.